Modern concepts in innovation and their impact on the policy of shaping innovation from the European perspective - Al Mahmoud, Aisha Mohammed; Mako, Saba; Eilachi, Miklush (Journal of Humanities & Social Sciences, 2018)
The ambition of the paper is to examine the dominant and the recently emerging new concepts of innovation and indicate their impacts on the innovation policy formation. The definition of innovation policy depends on the theoretical foundations of innovation. This means that all choices policy makers take in elaborating innovation policies have their more or less direct theoretical implications. In order to understand innovation policies in Europe at different (European and national) levels, we have to understand the theoretical choices and assumptions that are implicitly or explicitly made. We can sketch two stylized approaches to innovation policies. In the paper we will briefly present these two approaches and complement this by the explanation of some basic notions of innovation theory. After summarizing the various characteristics of the narrow and broad innovation approaches the authors illustrate the growing role of the Employee Driven Innovation (EDI) in the innovation activity.